Building a strategic performance management model for enterprises investing to coastal urban projects toward sustainability - Huynh, Truc Thi-Minh; Pham, Anh-Duc; Le-Hoai, Long (International Journal of Strategic Property Management, 2021)
In addition to the sustainable development of coastal areas, the success of local corporations investing in coastal urban projects is significantly affected by severe sea level rises and extreme disasters. Investment companies should plan which objectives need to target to reduce uncertainty in the early project stages, track project execution, and assess project output as projects complete the construction phase and start operational activities. To assist enterprises in planning, evaluating, and monitoring project performance aligning with vision and strategy, this study contributes a strategic management tool developed by integrating the Balanced Scorecard (BSC), Analytic Network Process (ANP), and Decision Making Trial and Evaluation Laboratory (DEMATEL) methods. A case study of a well-known investment corporation in Vietnam illustrates the research approach. This research appreciated stakeholder’s satisfaction as the main consequence and human resource as the most prominent cause of coastal urban projects. Furthermore, the proposed model for Vietnam in this study could be referred by other developing countries to facilitate companies to plan, measure, evaluate, and control the organizational performances for the coastal urban project success.First published online 09 February 2021